(untitled) (Revista Torreón Universitario, 2022)
This article is configured from a reflective look at the reality assisted by a capitalist development system in which the meaning of life, happiness, and human fulfillment have been transposed towards having, dominion and power; an economic model framed in production and usufruct, in which the soft and delicate threads that weave the conditions of life on the planet have been broken and degraded and the humanist traces in the path of the human have been erased; which distorts its condition as a model of development and translates into social inequity, inequality, marginalization, and poverty. Thinking about how to mend the fabrics of life again and configure new humanist traces, requires defining an education whose inspiration is to make the condition of the human being worthy; to inhabit the school again as a scenario to conjugate with actions the verbs humanize and power and to rethink the meaning and essence of teaching and even the role of the teacher and the student from other perspectives, looks, and logics.